Personality traits and stress coping among obstetricians diagnosing and communicating fetal death: A cross‐sectional study. Issue 2 (11th December 2021) - Muin, Dana Anais; Erlacher, Janina; Leutgeb, Stephanie; Toth, Bettina; Felnhofer, Anna
Abstract: Objective: To assess obstetricians' personality traits (empathy, locus of control [LoC], situational affect) and relate these to stress coping when making the diagnosis and delivering the news of late fetal death to parents. Methods: Cross‐sectional questionnaire study. Results: 341 Austrian obstetricians (72.7% females) participated in this online survey. Participants' mean age was 46.4 ± 10.8 years. The majority of participants ( n  = 158, 46.3%) had been previously involved in the diagnosis of fetal death and subsequent breaking news up to five times. We observed no gender‐specific differences in physicians' stress coping, including situational affect, perceived stress, challenge, self‐concept, or perceived control, nor in internal or external LoC, and perspective taking. Female obstetricians showed significantly higher trait empathy and reported higher levels of distress regarding fetal death than males. Obstetricians with greater experience in dealing with fetal death (>11 times) reported a higher ability to cope with stress as reflected by lower situational affect, less perceived stress, less challenge, and higher situational control. Conclusion: While obstetricians' stress coping in diagnosing and communicating fetal death is independent of physicians' gender, greater ability to empathize with the parents diminishes overall sense of control and affect over the situation, whereas increased level of clinical experience with fetal death supports all domains of control and stress coping. Abstract : SynopsisThe contents of this page will be used as part of issue TOC only. It will not be published as part of main article. Synopsis Stress coping in diagnosing and communicating fetal death is independent of obstetricians' gender, yet clinical experience increases, while empathy diminishes, situational control and affect.